2001
DOI: 10.1053/jhep.2001.26513
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity of Intrahepatic Colorectal Metastases After Preoperative Hemihepatic Portal Vein Embolization

Abstract: Although hemihepatic portal vein embolization (PVE) has been used preoperatively to extend indications for hepatectomy in patients with colorectal metastases, the effects of this procedure on tumor growth and outcome remain controversial. To address this issue, we assessed the proliferative activity of intrahepatic metastases after PVE and the long-term outcome of this procedure. Eighteen patients with colorectal metastases underwent preoperative PVE between 1996 and 2000 (PVE group). Twenty-nine patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
216
0
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(239 citation statements)
references
References 31 publications
7
216
0
14
Order By: Relevance
“…In our meta-analysis there wasn t any statistical difference between the two types of surgeries in regeneration volume. As reported previously, the hypertrophy of the FLR is negatively correlated with the pre-PVE FLR volume (10). Because hepatic parenchyma transection is usually performed along the umbilical fissure (the segmental border between left lateral lobe and segment 4) in ALLPS procedure (4,11) while PVE is usually performed on right hemi-liver in TSH procedure (12,13).…”
Section: Discussionmentioning
confidence: 68%
“…In our meta-analysis there wasn t any statistical difference between the two types of surgeries in regeneration volume. As reported previously, the hypertrophy of the FLR is negatively correlated with the pre-PVE FLR volume (10). Because hepatic parenchyma transection is usually performed along the umbilical fissure (the segmental border between left lateral lobe and segment 4) in ALLPS procedure (4,11) while PVE is usually performed on right hemi-liver in TSH procedure (12,13).…”
Section: Discussionmentioning
confidence: 68%
“…PVE increases the anticipated future liver volume and allows surgery in patients who would otherwise be contraindicated for resection. The potential disadvantage of PVE is that earlier studies have suggested that it may stimulate tumour growth and lead to reduced long-term survival (Elias et al, 1999;Kokudo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour growth exceeding that of the normal liver parenchyma has been shown on imaging following PVE in patients with contra lateral lobe metastases (Elias et al, 1999), and the tumour-doubling time following PVE has been shown to be reduced from 92 to 76 days (Kokudo et al, 2001). There have been concerns that PVE may increase the risk of disease recurrence after curative resection (Kokudo et al, 2001;Pamecha et al, 2009). The influence of PVE on tumour growth characteristics on resected cancers has not been investigated.…”
mentioning
confidence: 99%
“…Therefore, several methods to increase the future remnant liver volume before major hepatectomy, including portal vein embolization (1), ligation (2), sequential arterial and portal vein embolizations (3), and two-staged hepatectomy (4), were introduced. These techniques, however, usually required 2-8 weeks interval before completing the entire clearance of tumor burden in the liver and the risk of tumor progression during the period might be critical especially among the patients with borderline resectable tumors or oncologically aggressive tumors (5,6).…”
Section: Introductionmentioning
confidence: 99%